2006
DOI: 10.1177/0193945905284723
|View full text |Cite
|
Sign up to set email alerts
|

Survey Response Inducements for Registered Nurses

Abstract: The past 20 years have seen an overall decline in survey response rates and an even more pronounced decline in samples of health care professionals. The authors tested the use of a "thank you" or "reminder" postcard as a method by which to stem the tide of declining response rates. The authors conducted a mail and telephone survey of 49,605 registered nurses for the 2000 National Sample Survey of Registered Nurses and sent an extra mailing to a random subsample (n = 4,968). They then compared response rates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…As tools that characterize employee perceptions in various health care settings are widely disseminated, 21 ramifications of design elements on issues of validity must be explored. In contrast to previous work that found the use of a simple reminder postcard had little impact on response rates from a large sample of nurses, 22 the value of multiple mailings was evident in the current study. Repeat mailings improved the racial and socioeconomic diversity of the respondent pool.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As tools that characterize employee perceptions in various health care settings are widely disseminated, 21 ramifications of design elements on issues of validity must be explored. In contrast to previous work that found the use of a simple reminder postcard had little impact on response rates from a large sample of nurses, 22 the value of multiple mailings was evident in the current study. Repeat mailings improved the racial and socioeconomic diversity of the respondent pool.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, some suggest mailing advance incentives to all potential participants as a way to increase response rates. 22 Future better-controlled studies should address this potential bias. Third, the survey questions addressed a potentially sensitive subject-patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, follow-up of nonrespondents was difficult as there was a limited period for data collection and responses were likely to be affected once the system went ''live.'' Also, there was a low response rate of the nurses, although other studies have reported this to be particularly challenging with healthcare professionals (Hill, Fahrney, Wheeless, & Carson, 2006), it still leaves some unanswered questions. Finally, the survey examined one hospital using a particular EMR system and interviewed nurses from the ICU=CCU only.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…It has been found that in surveys of the health care professionals, response rates are often influenced by respondents' characteristics and high workload demands. 47 Other limitations are similarly inherent to the use of surveys examining practice variation. For example, respondents may not practice in the manner that they indicate in the survey.…”
Section: Limitationsmentioning
confidence: 99%